Free trade agreement between People's Republic of China and India: Likely impact and its implications to Asian economic community - Swapan K. Bhattacharya; Biswa N. Bhattacharyay (Asian Development Bank Institute (ADBI), 2006)
Open regionalism and trade cooperation between the world's two largest developing countries, the People's Republic of China (PRC) and India, can foster outward-oriented development and intra-regional trade based on comparative advantage and available factor endowments. In view of the recent wave of worldwide subregional and bilateral trade cooperation, and the recent suspension of Doha negotiations by the World Trade Organization, the opportunity costs of not moving toward greater trade integration between the PRC and India could be increasing. This paper presents the recent trends in the PRC-India trade and examines empirically the likely impact of their preferential and free trade agreements using Gravity Model under different comparative-static scenarios. It also discusses the implications of PRC-India trade cooperation on the formation of the Asian Economic Community
Keywords: F1; F2; Q1; Q4; R4; 330; India; China; Economic Cooperation; Trade; Free Trade Agreement; Gravity Model; Asian Economic Community; Handelsregionalismus; Freihandelszone; Internationale Wirtschaftsbeziehungen; Gravitationsmodell; China; Indien